New Analytical Approach to Two-Dimensional Viscous Flow with a Shrinking Sheet via Sumudu Transform - RATHORE, Sushila; SHISODIA, Yadvendra Singh; SINGH, Jagdev (Walailak Journal of Science and Technology (WJST), 2013)
In this paper, a new analytical approach based on homotopy perturbation Sumudu transform method (HPSTM) to a two-dimensional viscous flow with a shrinking sheet is presented. The series solution is obtained by HPSTM coupled with Padé approximants to handle the condition at infinity. The HPSTM is a combined form of the Sumudu transform method, homotopy perturbation method and He’s polynomials. This scheme finds the solution without any discretization or restrictive assumptions and avoids round-off errors. The numerical solutions obtained by the proposed method indicate that the approach is easy to implement and computationally very attractive. doi:10.14456/WJST.2014.39